Effects of cardiorespiratory fitness and weight status on knowledge of physical activity and fitness, attitude toward physical education, and physical activity - Senlin Chen; Xiangli Gu (BMC, 2018)
Abstract Background The purpose of this study was to examine the effects of cardiorespiratory fitness and weight status on knowledge of physical activity and fitness (PAF knowledge), attitude toward physical education (PE), and physical activity. Methods A total of 343 middle school students participated in the study (Age: M/SD = 12.76/.94, ranging from 11 to 14 years old). PE Metrics™ was used to measure PAF knowledge, and Attitude toward Physical Education Questionnaire and Youth Activity Profile were used to measure attitude, physical activity and sedentary behavior. Fitness and weight status were assessed using FitnessGram and converted to in Healthy Fitness Zone (HFZ) or Not in HFZ. Results Two-way multivariate analyses of covariance (MANCOVA; gender and grade as covariates) showed a significant group effect for cardiorespiratory fitness (ΛPilla = .07, F 4,255 = 5.03, p = .001, ηp2 $$ η_p^2 $$ = .07) but not for weight status (p = .57). PAF knowledge (F 1,258 = 9.49, p < .01, ηp2 $$ η_p^2 $$= .04), attitude (F 1,258 = 4.45, p < .05, ηp2 $$ η_p^2 $$= .02) and sedentary behavior (F 1,258 = 6.89, p < .01, ηp2 $$ η_p^2 $$= .03) all favored the HFZ group. Conclusions The findings reinforce the importance of promoting cardiorespiratory fitness in middle school PE as students acquire attitude, knowledge, and behaviors needed for active-living.